RESPIRATORY AND SYMPTOMATIC IMPACT OF ASCITES RELIEF BY PARACENTESIS IN PATIENTS WITH HEPATIC CIRRHOSIS - WITTMER,Verônica Lourenço (2020)
ABSTRACT BACKGROUND: Liver cirrhosis is a highly prevalent disease that, at an advanced stage, usually causes ascites and associated respiratory changes. However, there are few studies evaluating and quantifying the impact of ascites and its relief through paracentesis on lung function and symptoms such as fatigue and dyspnea in cirrhotic patients. OBJECTIVE: To assess and quantify the impact of acute reduction of ascitic volume on respiratory parameters, fatigue and dyspnea symptoms in patients with hepatic cirrhosis, as well as to investigate possible correlations between these parameters. METHODS: Thirty patients with hepatic cirrhosis and ascites who underwent the following pre and post paracentesis evaluations: vital signs, respiratory pattern, thoracoabdominal mobility (cirtometry), pulmonary function (ventilometry), degree of dyspnea (numerical scale) and fatigue level (visual analog scale). RESULTS: There was a higher prevalence of patients classified as CHILD B and the mean MELD score was 14.73±5.75. The comparison of pre and post paracentesis parameters evidenced after paracentesis: increase of predominantly abdominal breathing pattern, improvement of ventilatory variables, increase of the differences obtained in axillary and abdominal cirtometry, reduction of dyspnea and fatigue level, blood pressure reduction and increased peripheral oxygen saturation. Positive correlations found: xiphoid with axillary cirtometry, degree of dyspnea with fatigue level, tidal volume with minute volume, Child “C” with higher MELD score, volume drained in paracentesis with higher MELD score and with Child “C”. We also observed a negative correlation between tidal volume and respiratory rate. CONCLUSION: Since ascites drainage in patients with liver cirrhosis improves pulmonary volumes and thoracic expansion as well as reduces symptoms such as fatigue and dyspnea, we can conclude that ascites have a negative respiratory and symptomatological impact in these patients.